Informal Sector Dynamics in Times of Fragile Growth : The Case of Madagascar - Vaillant, Julia; Grimm, Michael; Lay, Jann; Roubaud, François (World Bank, Washington, DC, 2017)
This paper investigates the dynamics of the informal sector in Madagascar during a period of fragile growth. Overall, the behavior of informal firms in terms of earnings, employment and capital accumulation points to a degree of heterogeneity which goes beyond a simple dualistic model and even a more refined model that would distinguish between an upper entrepreneurial and a lower subsistence tier within the informal sector. However, in line with the dualistic model, the informal sector indeed fulfills a labor absorbing function in times of crisis. During the growth period authors see capital accumulation in most of the sectors and lots of evidence that households expand their activities. However, this happens mainly through the creation of new firms instead of the expansion of existing ones, which is consistent with much higher returns at very low levels of capital. More rapid expansion can be observed in sectors that operate with lower capital intensity, which is also consistent with risk or credit constraints as major deterrents to expansion. While there is some indication that total factor productivity increased over time, returns to capital and labor where not higher at the end of the observation period than at the beginning. Returns are also rather low at high levels of capital. These findings point to a limited growth potential of the informal sector as a whole. The heterogeneity in capital returns hints at large inefficiencies in allocating capital across informal firms.